Gas-Phase Reactivity of Carboxylic Acid Functional Groups with Carbodiimides - Prentice, Boone M. (2012)
Gas-phase modification of carboxylic acid functionalities is performed via ion/ion reactions with carbodiimide reagents [N-cyclohexyl-N′-(2-morpholinoethyl)carbodiimide (CMC) and [3-(3-Ethylcarbodiimide-1-yl)propyl]trimethylaminium (ECPT). Gas-phase ion/ion covalent chemistry requires the formation of a long-lived complex. In this instance, the complex is stabilized by an electrostatic interaction between the fixed charge quaternary ammonium group of the carbodiimide reagent cation and the analyte dianion. Subsequent activation results in characteristic loss of an isocyanate derivative from one side of the carbodiimide functionality, a signature for this covalent chemistry. The resulting amide bond is formed on the analyte at the site of the original carboxylic acid. Reactions involving analytes that do not contain available carboxylic acid groups (e.g., they have been converted to sodium salts) or reagents that do not have the carbodiimide functionality do not undergo a covalent reaction. This chemistry is demonstrated using PAMAM generation 0.5 dendrimer, ethylenediaminetetraacetic acid (EDTA), and the model peptide DGAILDGAILD. This work demonstrates the selective gas-phase covalent modification of carboxylic acid functionalities.